2002
DOI: 10.1007/s00423-002-0296-8
|View full text |Cite
|
Sign up to set email alerts
|

Childbirth and incontinence: a prospective study on anal sphincter morphology and function before and early after vaginal delivery

Abstract: Vaginal delivery leads to direct mechanical trauma to the anal sphincters, while stretch and distension of the pudendal nerve seem to be of minor importance. Only endoanal ultrasonography is suitable for detection of occult sphincter lesions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
22
0
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(27 citation statements)
references
References 27 publications
4
22
0
1
Order By: Relevance
“…Nonetheless, our results suggest that women who have an episiotomy are at higher risk than those who have not of having a sonographic anal sphincter defect, and that women delivered with the assistance of uterine pressure are at higher risk of larger defects. In agreement with other research teams we found sphincter pressure to decrease soon after delivery (3,4,8,10), but to have recovered after 6 months. Our results suggest that the anal sphincter is longer during pregnancy than in the non-pregnant state (statistically significant difference), and that it may be slightly thicker (non-significant difference).…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Nonetheless, our results suggest that women who have an episiotomy are at higher risk than those who have not of having a sonographic anal sphincter defect, and that women delivered with the assistance of uterine pressure are at higher risk of larger defects. In agreement with other research teams we found sphincter pressure to decrease soon after delivery (3,4,8,10), but to have recovered after 6 months. Our results suggest that the anal sphincter is longer during pregnancy than in the non-pregnant state (statistically significant difference), and that it may be slightly thicker (non-significant difference).…”
Section: Discussionsupporting
confidence: 93%
“…After a vaginal delivery without a clinically recognised sphincter tear, endosonographic sphincter defects have been observed with a frequency of 7% to 41% (3)(4)(5)(6)(7)(8)(9)(10)(11). We have found 20% (5/25) of non-pregnant nullipara with no symptoms of anal incontinence to have sphincter defects at anal endosonography.…”
Section: Introductionmentioning
confidence: 69%
See 2 more Smart Citations
“…In addition, anal electrosensitivity normalized 6 months after uneventful delivery. Perception threshold and threshold for urgency measured by rectal balloon distension was not affected by childbirth [49]. …”
Section: Discussionmentioning
confidence: 99%